ANALISIS AKUNTANSI ASET TETAP BIOLOGIS PADA KELOMPOK TANI TERNAK MAJU BERSAMA LANDASAN ULIN - Suzi Suzana; Tina Lestari (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2020)
This study aims to conduct an accounting analysis of biological fixed assets in the Farmers Advanced Farmers Group which conducts biological asset recording activities without setting the acquisition price as a basis for measurement, because it is based on the consideration that it is more measurable when using estimates of applicable market prices. This research belongs to applied research with data analysis techniques carried out with qualitative analysis. The data that is processed becomes valuable information for Farmers groups related to the Treatment of Biological Fixed Assets in Determining Fair Value. Research Results Show that the Advanced Farmers Group carried out recording activities of biological assets without setting the acquisition price as a basis for measurement, because they considered the use of estimated market prices more measurable.